2022
DOI: 10.1093/aob/mcac098
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of long-distance signalling upon plant terrestrialization: comparison of action potentials in Characean algae and liverworts

Abstract: Background In this review, we summarize data concerning action potentials (APs) – long-distance electrical signals in Characean algae and liverworts. These lineages are key in understanding the mechanisms of plant terrestrialization. Liverworts are postulated to be pioneer land plants, whereas aquatic Charophytes are considered the closest relatives to land plants. The drastic change of the habitat was coupled with the adaptation of signalling systems to the new environment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 145 publications
0
3
0
Order By: Relevance
“…TEA inhibits depolarization of cell membrane potential in Conocephalum conicum and Physcomitrium ( Physcomitrella) patens (Trebacz et al 1989, Johannes et al 1997). In Conocephalum , the equilibrium potential of K + is higher than the resting membrane potential, opening of the K + channel may induce depolarization of the membrane potential (Trebacz et al 1994, Kisnieriene et al 2022). Furthermore, simultaneous measurement of [Ca 2+ ] cyt and surface potential revealed that these two signals are tightly interconnected (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…TEA inhibits depolarization of cell membrane potential in Conocephalum conicum and Physcomitrium ( Physcomitrella) patens (Trebacz et al 1989, Johannes et al 1997). In Conocephalum , the equilibrium potential of K + is higher than the resting membrane potential, opening of the K + channel may induce depolarization of the membrane potential (Trebacz et al 1994, Kisnieriene et al 2022). Furthermore, simultaneous measurement of [Ca 2+ ] cyt and surface potential revealed that these two signals are tightly interconnected (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative transcriptomics of amphibious plants grown submerged versus on land reveal differentially expressed genes involved in underwater acclimation like cuticle and stomatal development, cell elongation, and modi ed photosynthesis [8]. Genomics has also uncovered key roles of plant hormones in regulating heterophylly [13]. Moreover, comparative genomics between aquatic and terrestrial species identify genomic signatures enabling adaptation to submerged life, including changes in submergence tolerance, light sensing, and carbon assimilation genes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Comparative transcriptomics of amphibious plants grown submerged versus on land reveal differentially expressed genes involved in underwater acclimation like cuticle and stomatal development, cell elongation, and modified photosynthesis [ 8 ]. Genomics has also uncovered key roles of plant hormones in regulating heterophylly [ 13 ]. Moreover, comparative genomics between aquatic and terrestrial species identify genomic signatures enabling adaptation to submerged life, including changes in submergence tolerance, light sensing, and carbon assimilation genes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%